2019
DOI: 10.1292/jvms.18-0582
|View full text |Cite
|
Sign up to set email alerts
|

Schmallenberg virus induces apoptosis in Vero cell line via extrinsic and intrinsic pathways in a time and dose dependent manner

Abstract: Schmallenberg virus (SBV), discovered in 2011 in Germany, is associated with clinical manifestations of fever, diarrhea, reduced milk yield, abortions and congenital malformations in ruminants. Despite many studies performed for SBV, there is no detailed research on in vitro apoptotic effect of SBV. This study is aimed to determine apoptosis pathways and role of pro-apoptotic and anti-apoptotic molecules in Vero cells infected with SBV. The study results showed that SBV induced apoptosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…SBV infects ruminants and causes hyperthermia and diarrhea and decreases milk supply. Symptoms of the infection include, but are not limited to, abortions and congenital anomalies such as hydranencephaly, scoliosis, brachygnathia, hydrocephalus, and arthrogryposis [ 122 , 123 , 124 ].…”
Section: The Role Of Bcl-xl In Schmallenberg Virus Infectionmentioning
confidence: 99%
See 2 more Smart Citations
“…SBV infects ruminants and causes hyperthermia and diarrhea and decreases milk supply. Symptoms of the infection include, but are not limited to, abortions and congenital anomalies such as hydranencephaly, scoliosis, brachygnathia, hydrocephalus, and arthrogryposis [ 122 , 123 , 124 ].…”
Section: The Role Of Bcl-xl In Schmallenberg Virus Infectionmentioning
confidence: 99%
“…The most important question is its influence on infected cell viability. Aksoy and Azkur [ 123 ] have studied the impact of SBV on the apoptotic potential of Vero cells. The research revealed that SBV infection triggered the intrinsic and extrinsic apoptosis pathways.…”
Section: The Role Of Bcl-xl In Schmallenberg Virus Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The explanation of this mechanism shall serve as a guide for the treatment of severe patients. Apoptosis of lymphocytes is regulated by pro and anti-apoptotic mechanisms through endogenous and exogenous factors (19).…”
Section: Discussionmentioning
confidence: 99%
“…SBV (strain F6; GenBank accessions KC355457–KC355459 represent sequences from the 3 segments of SBV), from the laboratory of Dr. Wim H. M. van der Poel (Wageningen Bioveterinary Research), was propagated in Vero cells at 37°C in 5% humidified CO 2 . SBV propagations were confirmed by RT-PCR with 382-469 primers 5 and a plaque titration 1 assay (Suppl. Fig.…”
mentioning
confidence: 99%